(untitled) (Research, Society and Development, 2020)
The objective was to understand the youth’s experience in HIV diagnosis and their expectations with antiretroviral treatment. Qualitative research, with a phenomenological approach, based on Martin Heidegger’s theoretical-philosophical-methodological referential. Data production took place through phenomenological interviews with ten participants aged between 16 and 23 years in a specialized service located in a university hospital in Rio Grande do Sul, Brazil. The units of meaning were: discovering the HIV diagnosis means a shock, but you have to understand and live life; and treatment with antiretrovirals means expecting to continue living and planning the future. The young person’s experience in discovering HIV revealed the fact of having a diagnosis that they cannot change and to accept it they need time and support. The expectation with antiretroviral treatment revealed the occupation with self care routine makes it possible to live, be healthy, plan the future and carry out the plans. Understanding the meaning of ARV treatment for youth helps guide care, and it is important to rethink the daily care behavior provided to this population.